PWE-159 Diabetes and Pancreatic Cancer – Cause or Association?. (17th August 2016) - Chen, L; Kumar, M
Abstract : Introduction: Diabetes is an established risk factor for pancreatic cancer. 1 However, there is still limited evidence around predictors of pancreatic cancer diagnosis and severity in patients with pre-existing diabetes. In this retrospective observational study, we assess the relationship between pre-existing diabetes and pancreatic cancer in a UK patient cohort. In particular, we investigate the association of pre-diagnosis blood glucose levels with onset and severity of pancreatic cancer to determine whether there is a role for screening in diabetic patients. Methods: Between 2012 and 2014, a total of 188 patients were diagnosed with pancreatic cancer at our regional oncology centre. Data was available for 116 of these patients. Detailed information on pre-diagnosis diabetic status, plasma glucose levels and cancer severity were retrieved systematically from their clinical notes and cancer services database, using standardised forms and procedures. Multivariate logistic regression analysis was used to investigate the association of blood glucose levels 5 years pre-diagnosis with age of cancer diagnosis and TNM staging of the cancer. Results: Overall, the mean age of diagnosis was 70.8 years and 30% of these patients had pre-existing diabetes, compared to the UK national prevalence of 16.3% (men) and 9.4% (women) for a similar age range (65–74 years). 2 Among those who had died by the time of analysis (n = 37), the age at diagnosis of cancer was 2.4 years younger in patients with pre-existing diabetes than those without. Mean highest blood glucose level 5 years before diagnosis (n = 93) was 7.17 mmol/l in non-diabetics and 15.14 mmol/l in patients with diabetes. Each 1 unit increase of log-transformed blood glucose, regardless of diabetes status, was associated with a 2 year earlier age of diagnosis (p = 0.32) and 4 fold increase of having TNM stage T4/N1/M1 or greater (p = 0.22). Conclusion: Our study suggests that pancreatic cancer patients had a much higher prevalence of pre-existing diabetes compared with the general population. Raised blood glucose levels appeared to be associated with earlier age of onset, worse staging and prognosis of pancreatic cancer. This study highlights the need for further UK studies to investigate the relationship between high pre-diagnosis blood glucose levels and pancreatic cancer in order to further examine the role of screening in diabetic patients. References: 1 Muniraj T, Chari ST. Diabetes and pancreatic cancer. Minerva Gastroenterol Dietol . 2012 December;58 (4):331–345. 2 Health Survey for England 2011. HSE 2011: Vol 1, Chapter 4: Diabetes and Hyperglycaemia. Disclosure of Interest: None Declared